2012
DOI: 10.1002/cne.23103
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of tachykinins and their association with kisspeptins in the brains of zebrafish

Abstract: The tachykinins are a family of neuropeptides, including substance P (SP), neurokinin A (NKA), and neurokinin B (NKB), that are encoded by the tac1 (SP and NKA) or tac2/3 (NKB) genes. Tachykinins are widely distributed in the central nervous system and have roles as neurotransmitters and/or neuromodulators. Recent studies in mammals have demonstrated the coexpression of NKB and kisspeptin and their comodulatory roles over the control of reproduction. We have recently identified two kisspeptin-encoding genes, k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
52
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 128 publications
(50 reference statements)
9
52
1
Order By: Relevance
“…Our findings support the role of NKBs as neuroendocrine regulators of reproduction in fish. In contrast to mammals, which have only one TAC3 gene, goldfish and zebrafish (Biran et al, 2012;Ogawa et al, 2012;Zhou et al, 2012) have two TAC3 genes, consistent with the notion that there was a teleost-specific genome duplication event (Christoffels et al, 2004). The two goldfish TAC3 genes are predicted to generate four mature NKB peptides.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Our findings support the role of NKBs as neuroendocrine regulators of reproduction in fish. In contrast to mammals, which have only one TAC3 gene, goldfish and zebrafish (Biran et al, 2012;Ogawa et al, 2012;Zhou et al, 2012) have two TAC3 genes, consistent with the notion that there was a teleost-specific genome duplication event (Christoffels et al, 2004). The two goldfish TAC3 genes are predicted to generate four mature NKB peptides.…”
Section: Discussionsupporting
confidence: 60%
“…Increasing evidence supports a critical role of the NKB/NK3R system in mammalian reproduction (Corander et al, 2010;Ramaswamy et al, 2010Ramaswamy et al, , 2011Topaloglu et al, 2009); however, studies on NKBs in lower vertebrates are limited to zebrafish (Biran et al, 2012;Ogawa et al, 2012;Zhou et al, 2012). In the present study, we cloned and characterized two goldfish TAC3 cDNAs, determined their mRNA expression patterns and regulation in the brain and pituitary and examined the effects of in vivo administration of NKBs on GnRH and gonadotropin subunit mRNA expression.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The dHbL was implicated in mediating fear responses of zebrafish (57) comparable to the role of the rodent medial dorsal (SP) subnucleus, suggesting functional homology between these brain regions. However, because tac1 transcripts were not detected in the zebrafish Hb (58) and their cholinergic nature was also unresolved (13)(14)(15), functional comparisons with the mammalian Hb were incomplete.…”
Section: Resultsmentioning
confidence: 99%
“…The mammalian TAC1 and TAC4 give rise to 2 active neuropeptides, whereas the TAC3 is the only TAC that give rise to only 1 neuropeptide, namely NKB (17). We have recently identified genes encoding NKB (tac3a/b) and tac3r from many fish species, and cloned 2 tac3 cDNA forms from zebrafish (18,19). Phylogenetic analyses showed that piscine and mammalian Tac3 genes arise from 1 lineage (18).…”
mentioning
confidence: 97%